PHYSICAL GROWTH OF CHILDREN IN VORONEZH REGION. ITS DYNAMICS AND TRENDS - A.I. Ivannikov; V.P. Sitnikova; A.N. Pashkov ("Paediatrician" Publishers LLC, 2007)
Physical growth of children is one of the most important dices for the health status of the younger generation. The study of the children's physical growth and development peculiarities in the changing social and economic conditions is deferred to the key problems of the hygiene and health protection of children and adolescents. The object of the study was he children of Voronezh region. The authors estimated the ain indices of the physical growth: height and body mass. They amined over 12 000 children: 6310 boys and 6242 girls aged between 0 and 14 years, living in the urban and rural areas. Such studies never took place in Voronezh region in a capacity like this, as well as in such a variety of sample and high degree of their representativeness (р < 0,01). The acquired data on the physical growth of children in Voronezh region in the end of the 2nd millennium demonstrates a more favor able situation (towards the capital social and economic sphere) in the region, where the children population under the study resides, if compared with the beginning of the 20th century, as well as the advantage of influence on the physical growth of biological, medical and genetic factors over the social and hygienic ones (lifestyle, environment and etc.).Key words: physical growth, children, height, body mass.